MOTIF PENGGUNA DALAM MEMANFAATKAN AKUN TWITTER KELAS SEBAGAI MEDIA KOMUNIKASI ONLINE - Dewi, Nilam Chandara; Hastasari, Chatia; Wisudawanto, Rahmat (JURNAL KOMUNITAS, 2014)
Nowdays, one of the well-known means of communication is internet or also known as the new media. The internets is used as a main source for communicating and searching for information. This very media is what no longer makes distance and time a problem. The internet has developed and become an efficient and effective way of communication. The internet has grown into a communicative mean and cannot be disregarded. Internet users are mostly students, due to the facilities being easy to use and accessed. Most people use internet connection to receive information and entertainment. Accordingly to the Mcquail application which states that there are four motives on the usage of media, 1. Information (surveillance) with four subs: a. seeking news regarding events and conditions relevant with the closest environment, society, and the world.b.Seeking for guidance on practical issues, opinions and such which are related with choosing an option, c.To fulfill curiosity and public interest, d. To learn, self- education, 2. Personal identity motives consists of four subs: a. To find support on personal values,b.To find a behavior model, c.To identify oneself with other values found within the media, d.To gain an understanding of oneself. 3. Integration and social interaction motives (Personal Relationship) consists of six sub chapters: a. To obtain knowledge regarding the circumstances of others, b. To identify oneself with others and gain a sense of belonging, c.To find conversation material and social interaction, d. To gain friends beside humans, e. To assist social role, f. Makes connecting with family, friends and society possible. 4. For entertainment motives (Diversion) there are five sub chapters: a. To release oneself from problems, b.To relax, c.To achieve spiritual joy and esthetical joy, d. To fill time, e.To channel emotions, f. To stimulate sexual desires. It may be concluded that the aforementioned theories stated by McQuail are proven by twitter accounts of class XI class of 2013 students of SMA Negeri Surakarta within the period of November until December, aside from that the writer has also found changing motives which happens within information motives and entertainment motives